STRUKTUR FUNGSIONAL LEGENDA PERSEORANGAN MUNING SEKAMIS DI DESA SEKAMIS KECAMATAN CERMIN NAN GEDANG KABUPATEN SAROLANGUN PROVINSI JAMBI DAN INYIAK SUSU SABALAH DI KANAGARIAN KOTO GADANG KECAMATAN TANJUNG RAYA KABUPATEN AGAM PROVINSI SUMATRA BARAT - Indah Galang Dana Pertiwi; Hasanuddin WS Hasanuddin WS (Jurnal Bahasa dan Sastra, 2019)
This study aims to describe the similarities and differences in functional structure of the Legendary Individual Muning Sekamis and Inyiak Susu Sabalah. The data in this study are the functional structure of folklore personal legend Muning Sekamis and the functional structure of the individual legend Inyiak Susu Sabalah. The findings of this study, show that the folklore legend of Muning Sekamis and Inyiak Susu Sabalah based on functional structure, can be formulated in ten functions of the actors arranged in three situations, namely the initial situation, the situation of transformation, and the final situation. In the initial situation there are three functions of the performer, namely (a) living as an ancestor, (b) living and becoming an ancestor with other family members, (c) where the origin is unknown. In a transformation situation there are three functions of the performer, namely (d) only has one breast, (e) the breast is very long, (f) milk from her breasts can treat various diseases. In the final situation there are four functions of the perpetrator, namely (g) disappearing (turned off) at the end of the story, (h) installing a four-angle talisman, (i) a four-angle talisman has never been revoked until now, (j) the village where he lives with his descendants is called as a lost village. The functional structure of an individual folklore legend of Muning Sekamis is more complete, while the folklore legend of the individual Inyiak Susu Sabalah has a simpler functional story structure.